2017
DOI: 10.1021/acsami.7b05662
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of Endocytosis and Intracellular Trafficking of Semiconducting Polymer Dots

Abstract: Semiconducting polymer dots (Pdots) have shown great promise in biomedical applications, including biosensing, drug delivery, and live imaging of cells and biomolecules. Insight into the mechanism and regulation of cellular uptake and intracellular metabolism of Pdots is important for the development of superior Pdots-based theranostic nanoconjugates. Herein, we performed real-time imaging of endocytosis and intracellular trafficking of a type of fluorescent Pdots that showed excellent biocompatibility in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“… 10 Previous work has indicated that treating cells with endocytosis inhibitors could effectively inhibit various endocytotic pathways, for example, endocytic chlorpromazine (CPZ, interfering with clathrin-dependent endocytosis) 33 , 34 and methyl-β-cyclodextrin (MβCD, disrupting caveola-dependent endocytosis). 35 , 36 We also found that CPZ or methyl-β-cyclodextrin could reduce the cellular uptake of liposomes by L1210 and HeLa cells (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 69%
“… 10 Previous work has indicated that treating cells with endocytosis inhibitors could effectively inhibit various endocytotic pathways, for example, endocytic chlorpromazine (CPZ, interfering with clathrin-dependent endocytosis) 33 , 34 and methyl-β-cyclodextrin (MβCD, disrupting caveola-dependent endocytosis). 35 , 36 We also found that CPZ or methyl-β-cyclodextrin could reduce the cellular uptake of liposomes by L1210 and HeLa cells (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 69%
“…The dose of each inhibitor was chosen according to previous studies. [23][24][25]33,34 Aer 2 h treatment with these inhibitors, the culture medium was removed, and fresh medium containing FCNPs (20 mg mL À1 ) was added to the cells, which were maintained for another 2 h. 21 Endocytosis inhibitors were incubated with BY-2 cells for 2 h. The inhibitors were 30 mM chlorpromazine, 20 mM methyl-b-cyclodextrin, 10 mM wortmannin, and 37 mM genistein. Cells were washed three times with PBS aer removing inhibitors by a cell strainer (40 mm).…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%
“…Similar results have been published for other types of nanoparticles such as silicas and polymer dots. 23,44,45 We further investigated endocytic processes of FCNPs.…”
Section: Cellular Uptake Research By Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pdots can be ingested in large amount by macrophages rapidly, the amount and speed of Pdots uptake by epithelial cells are much more limited. Moreover, following endocytosis, majority of Pdots are transported and destined into lysosomes, implying that bioactive cargos, such as DNA, RNA and proteins, are unlikely to keep their intracellular functionality …”
Section: Introductionmentioning
confidence: 99%